2015
DOI: 10.1111/jgh.12716
|View full text |Cite
|
Sign up to set email alerts
|

No increased risk of hepatocellular carcinoma in cirrhosis due to Wilson disease during long‐term follow‐up

Abstract: Background and Aims: Data on risk of hepatocellular carcinoma (HCC) in patients with Wilson disease are scarce. We determine HCC risk in a well-defined cohort of Wilson patients. Methods: All patients with a confirmed diagnosis of Wilson disease (Leipzig score ≥ 4) in three Dutch university referral hospitals were included in this retrospective cohort study. End of follow-up was defined as date of diagnosis of HCC, liver transplantation, death, or last available hospital visit. Also, a meta-analysis was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 24 publications
0
28
1
2
Order By: Relevance
“…In addition, HCC has been reported in patients with Wilson disease. However, a recent report indicated that the risk of HCC was low in Wilson disease even in cases of cirrhosis [65]. …”
Section: Risk Factors For Hccmentioning
confidence: 99%
“…In addition, HCC has been reported in patients with Wilson disease. However, a recent report indicated that the risk of HCC was low in Wilson disease even in cases of cirrhosis [65]. …”
Section: Risk Factors For Hccmentioning
confidence: 99%
“…Copper accumulation in WD is said to be protective against tumorigenesis. The estimated annual risk of HCC from a Dutch study on 140 adults with WD followed up over 15 years was calculated to be 0.09%[ 84 ]. From another multicenter European study of 1186 WD patients, the prevalence of HCC was found to be 0.67%[ 85 ].…”
Section: Pathogenic Risk Factorsmentioning
confidence: 99%
“…[88][89][90] Some authors do not advocate routine hepatoma surveillance in cirrhosis related to Wilson's disease. 8,91 In practice however, clinicians will often opt for hepatoma surveillance, especially in the elderly.…”
Section: Initial Therapymentioning
confidence: 99%